From Crisis to Opportunity: The Barriers to Chinese National Sign Language Acceptance Among Hearing and Speech-Impaired Persons in China Amid the Pandemic - Wenwen Li; Sining Chen; Wenxin Zheng; Yinghua Chen; An Chen (SAGE Open)
The outbreak of COVID-19 emphasized the worldwide challenges in emergency communication, especially for Hearing and speech-impaired persons (HSIPs) with communication difficulties. In China, the epicenter of the initial outbreak, HSIPs faced significant communication barriers early on. Promoting the Chinese National Sign Language (CNSL) emerges as a potential solution to this predicament. Despite its potential, CNSL’s adoption rate in China is lower than expected, underlining the need to understand the barriers to its acceptance. Through collaboration with the Disabled Persons’ Federation in Yancheng District, Luohe City, Henan Province, we distributed an online survey via official disability WeChat groups to gather data from HSIPs. The survey design, incorporating single-choice questions for demographic information and a Likert five-point scale to gage the willingness to use CNSL, was intended not only to understand their basic situation but also to identify the determinants influencing HSIPs’ behavioral intention toward CNSL adoption. By using linear regression analysis with SPSS, we found that Perceived Usefulness (PU), Ease of Use (EOU), Social Influence (SI), Facilitating Conditions (FC), and Self-efficacy (SE) all have a significant positive impact on Behavioral Intention to Use (BIU) CNSL. Additionally, one-way ANOVA and post hoc tests revealed significant group differences between annual income and behavioral intention to use CNSL. This research provides profound insights for the global community regarding the acceptance of CNSL among HSIPs in China, offering insights to enhance daily and emergency communication efficiency for HSIPs, and contributing to building a more inclusive and safe society.